FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) PROVINSI SUMATERA BARAT - oktari, Dea; Yolamalinda, Yolamalinda; jolianis, jolianis (Pendidikan Ekonomi, 2014)
ABSTRACTRegional Income is one of the indicators that determine the degree of independence of a region. The greater acceptance of the original income of an area the lower the level of dependence of the local government to the central government. This study aimed to describe the motor vehicle tax receipts, Levy Market, and Total Population of the Local Revenue West Sumatra Province. This type of research conducted in this study is descriptive associative. The type of data used and time-based quantitative data was collected using a pooling or panel that is a combination of time series data (time series) with several places (crossing) the data form the panels are stacked by cross-section of data. Data used are secondary data obtained from the Central Statistics Agency (BPS) and the Office of Financial Management West Sumatra. Hypothesis testing is used t test, F test, and koefisisen of determination (R2).Based on the results of hypothesis testing and t Tax Motor Vehicle Population positive and significant impact on the original income, and t test market levies no significant effect on the original income. While the F-test together positive effect and significant correlation between motor vehicle tax, levies Market and Population of the original income. Effect of the magnitude of Motor Vehicle Tax, Levy Market and Population of the revenue is 75.2% and the remaining 24.8% is influenced by other variables not included in this research model.